Real effects of financial crises in Latin America - Bebczuk, Ricardo Nestor (2004)
Financial crises have become part of the economic landscape around the world and in Latin America in particular. Substantial effort is being nowadays devoted to understand and prevent crises, but less work has been advanced on their economic consequences. The conventional wisdom has been that crises inflict profound and lasting, harmful effects throughout the economy, yet only fragmentary evidence is available. This chapter is aimed to fill this void by bringing forward an integrated analysis of the different channels through which financial crises can hit the economy, providing in each case a basic conceptual framework, a succinct review of the existing international evidence, and some new results with an emphasis in Latin American and Caribbean nations. The structure of the chapter will be as follows: In Section 1, some introductory definitions regarding the elusive concept of financial crisis are provided; the effects on the banking system’s balance sheet will be the subject of Section 2, with an emphasis on four recent Latin American crises. This analysis will set the ground for subsequent work. Section 3 will present evidence on crisis-related fiscal costs and their effectiveness. Section 4 will go over the short- and medium-term macroeconomic effects, with Section 5 devoted to long-term economic growth. Some conclusions and lessons close.